Effectiveness Test of Stroke Risk Detection Application Model, Stroke Risk Scorecard - Tarwoto, Tarwoto; Rahmawaty, Elsye; Argianto, Argianto; Yusro, Muhammad (Riviera Publishing, 2023)
Stroke is a disease caused by impaired blood circulation to the brain. This disease is a non-communicable disease that can be prevented by controlling stroke risk factors. STRIC (Stroke Risk Score Card) is a stroke risk detection application resulting from the development of a stroke risk detection model by the National Stroke Association. This study aims to determine the sensitivity, specificity, and accuracy of the application of the early stroke risk detection model (STRIC) in detecting stroke risk. Descriptive analytics by conducting stroke risk assessment using the Stroke Risk Scorecard (STRIC) App. The total sample was 60 people, consisting of 30 post-stroke people and 30 non-stroke people. The sensitivity value of the STRIC application is 91.67% which means that the ability to predict stroke risk for those who have experienced a stroke is very high. The specificity value of the STRIC application was 77.78%; this means that the measurement capability of the STRIC application provides a non-stroke (negative) result of 77.78% or very good. The accuracy value of the STRIC application is 83.33%, which means that the ability of the STRIC application to detect the risk of stroke in all subjects tested correctly is 83.33%. Applying the STRIC application can help prevent stroke and improve the prognosis for high-risk individuals.